Synthesis of medium and large phostams, phostones, and phostines - Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2023)
Phostams, phostones, and phostines are a series of 1,2-azaphosphaheterocycle and 1,2-oxaphosphaheterocycle 2-oxide derivatives. They are phosphorus analogues of lactams and lactones and important biologically active compounds. The strategies for the synthesis of medium and large phostams, phostones, and phostines are summarized. They include cyclizations and annulations. Cyclizations achieve ring construction through the formations of C–C, C–O, P–C, and P–O bonds in the rings, while annulations build the rings via [5 + 2], [6 + 1], and [7 + 1] fashions with the stepwise formation of two ring bonds. This review includes the recent syntheses of seven to fourteen-membered phostam, phostone, and phostine derivatives.
Keywords: azaphosphaheterocycle; oxaphosphaheterocycle; phostam; phostine; phostone